Effect of re-pelletization on structural, mechanical and superconducting properties of BSCCO superconductors - Safran, S.; Kilic, A.; Ozturk, O. (Springer Science and Business Media LLC, 2016)
We have examined the effect of re-pelletization on structural, mechanical and superconducting properties of high temperature superconducting (HTS) bulk samples using Bi1.85Pb0.35Sr2Ca2Cu3Oy stoichiometry. Conventional solid state reaction method is used for preparation of three different bulk samples. XRD measurement of the samples shows that a high percentage of high-T c phase is determined. Superconducting critical transition temperature of the samples have been obtained from the curves of ρ-T and χ-T. Vickers micro-hardness are also calculated for all samples. Re-pelletization has a positive effect on structural, mechanical and superconducting properties of bulk samples.